Clinical Association of Negative Lymph Nodes With Adjuvant Chemotherapy in Patients With T3N0 Rectal Cancer - Dongxu Lei; Zhanzhen Liu; Xinyi Kang; Ziwei Zeng; Hao Xie; Tanxing Cai; Fujin Ye; Li Xiong; Wenxin Li; Zhenxing Liang; Xiaobin Zheng; Shuangling Luo; et al. (Gastroenterology Research and Practice)
Conclusion: NLN count is an independent prognostic factor in patients with T3N0 rectal cancer. Patients with low NLN counts (NLN < 21) may benefit from adjuvant chemotherapy.